Microstructure development and mechanical behaviour of pure copper processed by the novel TWO-CAP procedure - KENTLİ, AYKUT; ÖĞÜT, SERKAN (My University, 2023)
In this study, thin-walled open channel angular pressing (TWO-CAP) technique was applied to pure copper specimens as a novel severe plastic deformation (SPD) method. The TWO-CAP process was applied to the specimens up to four passes. After each pass, the microstructural and mechanical characterization of the material was investigated by tensile and hardness tests along with OM, SEM, EDS, TEM and XRD analyses. As a result, a highly increase in the mechanical properties was obtained, in addition satisfactory grain refinement was observed in microstructures. Strength and hardness values were positively affected from the minimizing the grain sizes after TWO-CAP process. Another reason of the improvements in mechanical properties can be explained as the increase in dislocation density. Furthermore, the effect of the TWO-CAP process on the dislocation density of the material has been demonstrated by XRD and TEM analyses in nanoscale. Moreover, the strain equation has been developed analytically and the effect of each pass on strain was calculated. Finally, the effect of the process on the stress-strain properties of the material was examined by the numerical analysis method and the study was verified.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Mechanics of Materials; Mechanical Engineering; experimental analysis; grain size refinement; numerical analysis; severe plastic deformation; TWO-CAP